ANALISIS SISTEM AKUNTANSI DAN PENGELOLAAN KEUANGAN UMKMSTUDI KASUS PADA PABRIK OMAH OBLONG YOGYAKARTA - Masrukhan, M.; Zakiyah, Lizatul (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to analyze the accounting system and financial management of SMEs, with a case study of Omah Oblong Factory in Yogyakarta. A sound accounting system is a crucial factor in improving the financial performance of SMEs. This research adopts a qualitative approach with a case study method. Data were collected through in-depth interviews, direct observation, and financial document analysis. The results indicate that Omah Oblong Factory employs a basic manual accounting system, but it exhibits several weaknesses, such as limited use of information technology and financial literacy. Financial management demonstrates a clear separation between revenue and expenses, though it is not fully integrated. By enhancing the use of information technology and providing financial literacy training, Omah Oblong Factory is expected to improve the efficiency of its accounting system and financial performance. This study offers strategic recommendations for the development of SME accounting systems in the future.